Invasão celular por formas metacíclicas do Trypanosoma cruzi da cepa G (TcL) - Voss, Marciele Guerra [UNIFESP] (2020)
Studies on cell invasion by Trypanosoma cruzi metacyclic forms have been made main ly with CL strain (genetic group TcVI). Available information about that strain does not apply to G strain (genetic group TcI). The objective of this work was to investigate the role of G strain surface glycoproteins (gp90 and mucin like molecules gp35/50) and host cell LAMP1 and LAMP2 proteins L ysosome A ssociated M embrane P roteins 1 and 2) in the invasion process. In assays in which HeLa cells were incubated with metacyclic forms, in absence or in the presence of gp35/50 mucins purified from G o CL strain , a significant inhibitory effect of G strain gp35/50 on parasite internalization was observed. Interaction of HeLa cells with G strain gp35/50 resulted in inhibition of lsosome spreading induced by nutritionally depleted medium. HeLa cells deficient in LA MP1 or LAMP2 were tested for susceptibility to invasion by metacyclic forms. As compared to wild type cells, LAMP1 deficient cells were significantly more resistant to invasion, whereas LAMP2 deficient cells presented an invasion rate similar to the contro l. As the surface molecule gp90, expressed on the surface of G strain metacyclic forms, is a member of gp85/trans sialidase superfamily, to which also belongs gp82 that binds to its receptor LAMP2, the possibility that LAMP1 might be the receptor for gp90 was examined. In co immunoprecipitation assays, in which extracts of metacyclic forms and of HeLa cells were incubated with magnetic beads coupled do anti gp90 monoclonal antibody, gp90 and LAMP1 were detected in the eluate (immunoprecipitate). Assays with magnetic beads coupled to anti LAMP1 antibody confirmed the binding of gp90 to LAMP1. The data of the study indicate the involvement of gp35/50 and possibily of gp90 in cell invasion by G strain metacyclic forms.